Features and driving factors of microbial metabolic limitation in mountain ecosystems in arid areas: A case study on the Helan Mountains, Northwest China - Pang, Danbo; Liu, Bo; Wu, Mengyao; Li, Xuebin; Hu, Yang; Ma, Jinpeng; Zhao, Wenzhi; Chen, Lin (Frontiers in Forests and Global Change, 2022)
Insights into what limits the growth of soil microorganisms in mountain ecosystems increase our understanding of microbial functions and processes. Although the distribution pattern of soil microorganisms in mountain ecosystems has been widely studied, their role in biogeochemical cycles along elevation gradients of mountain ecosystems in arid regions is poorly understood. In this study we analyzed the soil physicochemical properties, soil microbial community structure, extracellular enzymatic activities, ecoenzymatic stoichiometry, microbial metabolism, and their relationships along the 1,300–2,500 m elevational gradient of the Helan Mountains, northwest China. The results showed that the total microbial biomass and its components did not significantly vary with elevation. The GP:GN (gram-positive: gram-negative bacteria) ratios at low elevations were higher than those at the mid and high elevations, indicating enrichment of oligotrophic bacteria at low elevations. The five extracellular enzymes significantly differed with elevation gradient, while the levels of carbon (C)- and nitrogen (N)- acquiring enzymes first increased and then decreased with increasing elevations. Ecoenzymatic stoichiometry indicated that significant limitation of microbial growth by carbon (C) and phosphorus (P) levels occurred at high and medium elevations. Soil physicochemical characteristics, microbial community composition, and ecoenzymatic activities accounted for 43.94 and 22.21% of the microbial C and P restriction, respectively. Our study suggests that mountain ecosystems with high organic C storage possess abundant microbial populations limited by relative C and P. The study also provides important insights linking microbial metabolisms to the environmental gradients in arid mountain ecosystems.